Comparison between Different Anaesthesia Techniques for Protecting Renal Function in Children Undergoing Radical Nephrectomy - Muhammad Baqir Ali Khan, Tahir Nazeer, Usman Zeeshan, Rizwan Munir Ahmed, Amanullah Bhutto, Faizan Banaras (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Most primary renal neoplasms are caused by renal cell carcinomas (RCCs). There is a high risk of morbidity and mortality following radical nephrectomy due to acute kidney injury (AKI). It is crucial to detect and prevent this complication as early as possible. The present study aimed to anesthesia comparison after radical nephrectomy for kids: a study with different anesthesia techniques. Patients and Methods: This retrospective study was carried out on 84 children of the age up to 12 years undergoing radical nephrectomy in the department of Anaesthesiology, Chaudhary Muhammad Akram Hospital (CMA) Lahore during three years, from August 2019 to July 2022. Prior to study conduction, ethical approval was taken from research and ethical committee. Patients were allocated to three different groups: Group-D (Dexmedetomidine group), Group-C (Caudal group), and Group-P (Placebo group). Children were evaluated by taking history, physical examination, and laboratory examinations such as liver function, CBC, kidney functions, and coagulation profile. SPSS version 28 was used for data analysis. Results: A total of 84 children investigated with different anesthesia techniques. Each group was assigned 28 children undergoing radical nephrectomy. A significant difference did not appear between the three groups in terms of serum creatinine at any of the times of measurement. Group D showed significant lower values for cystatin C and NGAL compared with group C and group P regardless of the measurement period. In all three studied groups, there were no significant differences in age, gender, or weight of the patients (p> 0.05). Comparatively to the other two groups, the Dex Group had significantly higher urine output, more sedation, and lower objective pain scores. Conclusion: Clinical prediction schemes using cystatin C and NGAL biomarkers showed that dexmedetomidine prevents AKI in children undergoing renal replacement therapy. The Dex Group had significantly higher urine output, more sedation, and lower objective pain scores as compare to the other two groups. Furthermore, dexmedetomidine provides renal protection and sedation as well as analgesia. Keywords: Radical nephrectomy; Dexmedetomidine; Cystatin C; Children